2020
DOI: 10.3390/jcm9020303
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Micro-Computed Tomography and Cone-Beam Computed Tomography in the Assessment of Bone Quality and a Long-Term Volumetric Study of the Augmented Sinus Grafted with an Albumin Impregnated Allograft

Abstract: The purpose of our study was to compare micromorphometric data obtained by cone-beam computed-tomography (CBCT) and microcomputed-tomography (micro-CT) of the augmented sinus and to evaluate the long-term stability of the bone gain achieved using BoneAlbumin. Sinus lifts, and after 6-months, healing bone-biopsy and implant placement were carried out. Specimens were analyzed by micro-CT. A total of 16 samples were collected from nine patients (mean age 54.7 ± 6.5 years). Pre-, postoperative, and 3-year control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 44 publications
(70 reference statements)
1
12
0
Order By: Relevance
“…These results are consistent with the results of a previous CBCT study based on T.bTh values, however the observed Po(tot) values seem to be different, which might be due to different voxel sizes were used in the two studies. [41]. The microCT data of Kivovics et al are positively correlated with our CBCT results in regard of Po(tot) values, which might be caused by the higher resolution of CBCT imaging in the present investigation.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These results are consistent with the results of a previous CBCT study based on T.bTh values, however the observed Po(tot) values seem to be different, which might be due to different voxel sizes were used in the two studies. [41]. The microCT data of Kivovics et al are positively correlated with our CBCT results in regard of Po(tot) values, which might be caused by the higher resolution of CBCT imaging in the present investigation.…”
Section: Discussionsupporting
confidence: 80%
“…Micromorphometry analysis of CBCT images are reliable indicators of bone morphology, and its measurements correlate positively with microCT analysis of bone core biopsy samples [41]. BS/BV refers to the volume ratio of calcified tissues Po(tot) shows the total volume of open and closed pores [42].…”
Section: Discussionmentioning
confidence: 99%
“…Bone density measurements derived from CBCT reconstructions are inaccurate and should be generally avoided because of the artefacts and variable scanning conditions [ 36 , 37 , 38 ]. The literature suggests that micro-morphometric measurements based on CBCT data may be a reliable predictor of bone quality [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Consequently, in the present study, in addition to the grey level measurements of the CAIS software, bone density was determined by BV/TV measurements on the preoperative CBCT.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proven that albumin is necessary for early bone healing processes and is physiologically present in native bone [ 40 ]. Previous studies with SACBAs in the field of orthopedics and oral surgery have reported uncomplicated healing with a high degree of graft remodeling [ 17 , 19 , 41 ].…”
Section: Discussionmentioning
confidence: 99%